MILLIONAL GENERATION VS GENERATION Z VIEWS ON LATEST LITERATURE - Ni Kadek Karmaeni (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This article discusses the views of netizens according to time period. For humans, literary works are a form of expression of the contents of the heart expressed in written form. In this case, someone who expresses their heart in written literature is someone who wants to share a story for readers to feel. Short story/novel literary works are an outpouring of inner experiences regarding the phenomena of social and cultural life of society at that time. Literary works reveal events, ideas, and life values that are felt in them. Literature questions humans in all aspects of their lives so that works are useful for getting to know humans and their culture in a certain period of time. The development of a literary work based on time periods will change over time. From the results of data analysis regarding the views of a literary work, novels/short stories change every year. The views on the development of literary works according to the millennial generation and generation Z are very different. Based on the development of literature in each period, it is also called cutting-edge literature, where literary works from the 70-90s are works that include a national spirit in their works and are more expressive and use the Indonesian language fully. Periodization From each generation, we can learn how far Indonesian literature has developed.